The Effect of Charcoal on the Improvement of Grounding Resistance as a Soil Treatment in Reducing Grounding Resistance - Partaoanan Harahap Partaoanan Harahap; Waleed Khalid Ahmed Al-Ani (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2021)
Current technological developments are very competitive with each other, both in electric power distribution systems or electronic equipment. Disturbances that occur are usually caused by short circuits and ground disturbances, or lightning strikes. These disturbances will result in a voltage drop or increase in voltage, which results in decreased system stability, endangers people's lives, and can damage electronic equipment. Coconut Shell Charcoal has a lower resistivity value than soil and has a larger pore structure to absorb more water, and has conductive properties. The results obtained from the comparison using dry coconut shell charcoal and wet coconut shell charcoal show that measurements using wet coconut shell charcoal are better (less resistance) than using dry coconut shell charcoal. Soil resistivity measurements will be much better at the maximum depth than the usual depth (110 cm), better than 10cm.